Peran Guru Sebagai Teladan dalam Membentuk Karakter Siswa Pada Pendidikan Pancasila Di Kelas III SDN Kandangan 1/121 Surabaya - Eka, Rosa; Prameswari, Noviardani Kartika (Universitas Veteran Bangun Nusantara, 2025)
Abstract: The purpose of the researcher is to find out the importance of the role of teachers to shape the character of students at SDN Kandangan 1/121 and apply positive values in Pancasila education materials. This research uses a qualitative approach. The method applied is field research with the object of study at SDN Kandangan 1/121 Surabaya. In the process of collecting data, the author utilizes observation and interview methods. The results of the study show that the role of teachers in shaping student character includes 18 indicators that will be applied by students at SDN Kandangan 1/121 Surabaya.And by using Pancasila education learning materials which explain and provide examples in accordance with the precepts of Pancasila. With that, students are given examples of good deeds in the school environment by teachers, such as by obeying the rules in the classroom, and praying in congregation at school, practicing discipline by not being late for school Keywords:. Role of Teachers, Character Education, Pancasila Education.